Pengenalan Peran TNI AD melalui Mobile Game untuk Remaja - Aditya Satyagraha; Alfonzo Ronald Koapaha; Widihardjo Widihardjo (Wimba : Jurnal Komunikasi Visual, 2012)
Role of Indonesian Army (TNI AD) as military institution which was maintaining the sovereignty of the Unitary Republic of Indonesia (NKRI ) from all forms of threats was vital, and needed to be supported by other elements of nations, especially the young generation of Indonesia. Therefore we needed recognition and understanding of the role of the army to teenager in order to create synergy between the Army and the younger generation in an effort to defend the country. In this study, researcher was trying to provide information and knowledge about the role of the army to teenager through mobile game. The method which was used in this study was descriptive-qualitative method, the theory of communication which associated with the delivery of messages and information technology, and the Army as theme and content in the game. The technique was observations data and facts in the field than developed it into game of new theme of TNI AD. The purpose of this research was to design learning media and recognition of the role of the TNI AD by using turn-based strategy game. The preparation of this thesis performed an assessment of the technology, collected information about TNI AD, game concept, Android operation system, and another necessary supported concept. Then continued with analysis, system design, implementation and system testing. Result from this research was a game design, titled Jejak Garuda. This game was turn-based strategy game and played individualy in platform mobile device with Android operation system based. Visual game was created in 2D, in purpose to make it attractive and light for mobile device, but the gameplay was created as attractive as possible in order to make high replay value.